Experimental Research of Ions in Wound Healing Via Film Forming Solution - Kambampaty, Ketura; Setty, Nagesh Chandrashekhar; Naduvinamani, Suma; Khot, Kartik Bhairu; Sangi, Sibghatullah Muhammad Ali; Nagaraja, Sreeharsha; Meravanige, Girish; Islam, Mohammed Monirul; Sreenivasalu, Pavan Kumar; Chohan, Shahzad (Indian Journal of Pharmaceutical Education and Research)
Objectives: This study aimed to investigate the wound healing potential of Film Forming Solution (FFS) incorporated with Silver (Ag) and Copper Oxide (CuO) Nanoparticles (NPs). Materials and Methods: Ag NPs were synthesized by chemical reduction and CuO NPs by the co-precipitation method and optimized for concentration, pH, and temperature. Characterization was performed using UV-vis spectroscopy, FT-IR, particle size analysis, zeta potential, and SEM. Antibacterial activity was assessed by determining the MIC against Staphylococcus aureus and Escherichia coli. Optimized NPs were incorporated into a polymeric FFS and evaluated for various physicochemical properties. In vivo wound healing studies were carried out in Wistar rats for 21 days, and histopathological examinations were conducted to assess tissue regeneration. Results: Ag NPs exhibited a Surface Plasmon Resonance (SPR) peak at 432 nm with an average size of 72.61 nm, while CuO NPs showed strong absorption at 262.5 nm with a size of 105.5 nm. Zeta potential values were –27.3 mV for Ag NPs and –10.2 mV for CuO NPs, suggesting moderate colloidal stability. SEM revealed spherical, clustered Ag NPs and irregularly shaped CuO NPs. MIC values displayed broad spectrum activity of these NPs. In vivo wound healing studies revealed that control animals achieved 91.67 ± 0.88% wound closure, blank FFS-treated animals 83.44 ± 0.80%, standard-treated animals 99.44 ± 0.11%, Ag-FFS 99.0 ± 0.19%, and CuO-FFS 98.89 ± 0.22%. Conclusion: These findings highlight their potential as advanced topical delivery systems for safe and effective wound management.
Keywords: Copper oxide; Film-forming solution; Nanoparticles; Silver; Wound healing